2022
DOI: 10.7759/cureus.27422
|View full text |Cite
|
Sign up to set email alerts
|

Another Case of Bell's Palsy Recurrence After Pfizer-BioNTech COVID-19 Vaccination

Abstract: Twenty-seven months into the current pandemic and 18 months after vaccinations were made available, there are still relatively limited data on the incidence of recurrent Bell's Palsy after the administration of mRNA-based vaccines. The authors continue to believe that it is through rigorous reporting that the true incidence can be tabulated eventually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Researchers have proposed a potential link between recurrent Bell's and mRNA-based vaccines. 20 21 A retrospective cohort study indicated a strong association between mRNA COVID-19 vaccines and recurrent Bell’s palsy after a second vaccine dose. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proposed a potential link between recurrent Bell's and mRNA-based vaccines. 20 21 A retrospective cohort study indicated a strong association between mRNA COVID-19 vaccines and recurrent Bell’s palsy after a second vaccine dose. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Another reported case involved a 56-year-old woman who suffered an intracerebral hemorrhage in the left temporal lobe extending into the intraventricular space immediately after receiving the Pfizer-BioNTech COVID-19 vaccine. 74 Despite surgical efforts to clip a ruptured aneurysm, the patient unfortunately passed away on the second postoperative day.…”
Section: Hemorrhagic Complicationsmentioning
confidence: 99%
“…Nineteen FNP cases were reported following COVID-19 vaccination [110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] across the world. The patients' age ranged from 17 to 62 years (median (IQR): 38 (34, 57) years), 11 out of 19 patients were female (58%), and 4 patients had a prior history of FNP.…”
Section: Facial Nerve Palsymentioning
confidence: 99%